Ocena z zakresu ujawnionych informacji dotyczących wspólnych przedsięwzięć w sprawozdaniach finansowych przedsiębiorstw budowlanych - Tatarska, Marzena (The rstimation of the disclosed information concerning joint ventures in financial statements of building companies, 2008)
The article emphazies that the accounting principles have influence on financial information. On the basis of empirical research, the quality of information about joint ventures included in the financial statements is scrutinized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 74-83